Regional Approach to the Effects of the Production of Agricultural Holdings with Respect to the CAP Policy - Buks, Joanna; Pietrzykowski, Robert (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2014)
The productivity is a key issue in economics as it is one of the factors affecting the economic prosperity. An analysis of the agricultural production has a special place in economics of agriculture due to its high dependency on many factors. Therefore, many authors try to define what and to what extent affects the production in agricultural holdings. In their paper, the authors wanted to show that apart from basic production inputs, we also observe an impact of various types of payments on the production. These payments are used in agricultural holdings to cover costs related to the agricultural production, e.g. purchase of fertilisers and plant protection products. In the longer term, such activity may have negative consequences, namely it may result in the stagnation of the development of a holding. This is related to providing the holding with additional funds which protect it against bankruptcy and consequently delay making a decision on reorganising the holding. The paper also attempts to approach the analysed issue in spatial terms, because, as many authors notice, changes in the production and the system of payments are strongly diversified regionally. The studies used the spatial econometrics the SAR model. Based on the above model, an econometric production model, extended by various types of payments, has been proposed.